Being in the Past and Perform the Future in a Virtual World: VR Applications to Assess and Enhance Episodic and Prospective Memory in Normal and Pathological Aging - Rizzo, Azzurra; Gambino, Giuditta; Sardo, Pierangelo; Rizzo, Valerio (Frontiers in Human Neuroscience, 2020)
The process of aging commonly features a gradual deterioration in cognitive performance and, in particular, the decline of memory. Despite the increased longevity of the world's population, the prevalence of neurodegenerative conditions, such as dementia, continues to be a major burden on public health and consequently latest research has been focused on memory and aging. Currently, the failure of episodic and prospective memory is one of the main complaints in the elderly, considered among the early symptoms of dementia. It is therefore increasingly important to define more clearly the boundaries between normal and pathological aging. Recently, researchers have begun to build and apply virtual environments to the explicit purpose of better understanding the performance of episodic and prospective memory in complex and realistic contexts, with the perspective of further developing effective training procedures that depend on reliable cognitive assessment methods. Virtual technology offers higher levels of realism than “pen and paper” testing and at the same time more experimental control than naturalistic settings. In this mini-review, we examine the outcomes of recent available studies on virtual reality technology applications developed for assessment and improvement of episodic and/or prospective memory. In order to consider the latest technology, we selected 29 papers that have been published in the last ten years. These documents showed that VR-based technologies can provide valid basis for screening and treatment and, through increased sensory stimulation and enriched environments reproducing the scenarios of everyday life, could represent effective stimulating experiences even in pathological aging.